Transmissibility of a laminated rubber-metal spring: a preliminary study - Salim, Mohd Azli; Putra, Azma; Thompson, David J.; Ahmad, Nazirah; Abdullah, Mohd Azman (Trans Tech Publications Ltd., 2013)
This paper discusses the isolation performance of a laminated rubber-metal spring. A multi-degree-of-freedom-system model using mass-damper-spring components is developed to calculate its transmissibility due to only axial vibration in the spring. The results show the embedded layers of metal plate can improve the transmissibility at high frequency.